Raising awareness of antimicrobial resistance among the general public in the UK: the role of public engagement activities. Issue 1 (10th March 2020) - Redfern, James; Bowater, Laura; Coulthwaite, Lisa; Verran, Joanna
Abstract: In response to the accepted risk of emerging antimicrobial resistance, many organizations and institutions have developed and delivered events and activities designed to raise awareness of the issue and to change the behaviour of the intended audience. However, few of these events for a general public audience are documented or able to be sourced by those who might wish to repeat, adapt or modify, particularly those events that are successful. 'Insider knowledge' appears to be the best search tool. Moreover, evaluation of the success or impact of the event is rarely published. It would be useful if there were a 'hub' where descriptions of such activities could be deposited, enabling the building of a significant resource with real academic value.